(3fhQ GdCMjGA hJMaI GdCehGJs - (3eLghds ((3YHO GdeYWj Hf eMeO eWQLjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj Ye GdHdGO HfYeJg aEfj deG QCjJ bUhQ GdfGS aj WdH GdYde hGTJZGdge HeG dG jYfjge Cf CLeY dge eNJUQG fGaYG aj GdYHGOGJ MLeg UZjQ hYdeg cHjQ hfaYg ZRjQ jSJHUQ Hg GdeHJOj hjJPcQ Hg GdefJgj s
(3BNQgG (B:s
(3bGd Gdabg CHh GddjK QMeg Gddg JYGdi (B: (3jQGO ef GdYGde YTQ CTjGA GdNTjI hGdfUjMI hGdTabI hGdGMJeGd hGdUHQ hGdMde hGdJhGVY hGdYaI Yf CehGd GdfGS hGdOhGe Yi GdfXQ aj GdcJH hbqdI GdoMnqLGH hgh Cf jchf HGHg eaJhM ddhVjY hGdTQja hbO Je GdcJGHs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3Gdabg GdYGes